2021
DOI: 10.1002/jsfa.11346
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sensory properties driving consumers' liking of commercially available kale and arugula

Abstract: BACKGROUND: Kale and arugula are leafy green vegetables whose sensory properties have not been extensively explored. The objective was to assess the sensory properties and consumer acceptability of commercially available kale and arugula while also discovering drivers of consumer liking and barriers to consumer acceptance. Descriptive analysis and consumer testing were completed. The trained panellists (n = 11) were trained for 15 h to evaluate 11 sensory properties relating to the aroma, taste and texture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Recent work has identified important attributes in defining the differences in commercial arugula and kale varieties, some of which were labeled as ''baby'' plants (Barker et al, 2021). Our results confirmed the findings that bitterness is highly important in differentiating arugula and kale from different suppliers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Recent work has identified important attributes in defining the differences in commercial arugula and kale varieties, some of which were labeled as ''baby'' plants (Barker et al, 2021). Our results confirmed the findings that bitterness is highly important in differentiating arugula and kale from different suppliers.…”
Section: Discussionsupporting
confidence: 87%
“…Much of the recent descriptive work on baby and mature plants has focused on varieties that are widely available across North America, namely arugula and kale. A study from Barker et al (2021) found differences in several attributes such as earthiness, spiciness, and bitterness between commercial arugula samples labeled as ''baby'' varieties and those without this distinction, although the developmental stage of the plants was unknown. This highlights the need for descriptive research specific to ''baby'' plants and their differences from plants at other stages of development.…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates -Carbohydrates represent an important energy source for both plants and humans. Sugars, such as glucose and fructose, are a particularly important component of kale taste, which plays an important role in cultivar attractiveness, as kale is generally characterized as having a bitter and earthy flavor profile (Barker et al, 2022). Like other plants, kale possesses peak sucrose levels at ED, which in combination with transient leaf starch degradation, is vital for driving plant growth at night.…”
Section: Underlying Metabolic Differences Between Kale Cultivars Offe...mentioning
confidence: 99%
“…In general, the intent is to investigate the level of acceptance and the drivers of vulnerable consumers' choice 14‐16 . In detail: the first objective of this study was to understand vitamin D intake among Danish senior citizens (aged 55 years and above).…”
Section: Introductionmentioning
confidence: 99%